Cleavage of the dimeric cyclopalladated [Pd(N,C-dmba)(mu-X)](2), (dmba = N,N-dimethylbenzylamine; X = SCN and NCO) by diphosphines. Palladium(II) compounds with distinct structures in the solid-state and in solution - Ananias, SR; Mauro, A. E.; Neto, VAD (Kluwer Academic Publ, 2001)
The reactions of the pseudohalide-bridged dimer [Pd(N,C-dmba)(mu -SCN)](2) (1) (dmba = N,N-dimethylbenzylamine) with cis-Ph2PCH=CHPPh2 (cis-dppet) (1:1 molar ratio) and of [Pd(N,C-dmba)(mu -NCO)](2) (2) with Ph2PCH2CH2PPh2 (dppe) (1:2 molar ratio) gave mononuclear [Pd(C-dmba)(SCN)(cis-dppet)].H2O (1a) and [Pd(C-dmba)(NCO)(dppe)] (2a), respectively, with the diphosphines acting as chelating ligands. Reaction of (2) with Fe(C5H4PPh2)(2) (dppf) (1:1 molar ratio) yielded [{Pd(N,C-dmba)(NCO)}(2)(mu -dppf)] (2b), a bimetallic species containing two palladium atoms bridged by the diphosphine, whereas reaction in a 1:2 molar ratio gave the mononuclear [Pd(N,C-dmba)(dppf)][NCO]. CH2Cl2 (2c), with the diphosphine acting as a chelating ligand. The compounds have been characterized by elemental analysis, i.r., P-31{H-1}, C-13- and H-1-n.m.r. spectroscopies. Conductivity measurements together with spectroscopic data showed that (1a) and (2a) do not have the same structure in the solid state and in MeCl solution, whereas for compounds (2b) and (2c) no structural changes were observed when the solids were dissolved in MeCl.